P-Glycoprotein and Androgen Receptor Expression Reveals Independence of Canine Prostate Cancer from Androgen Hormone Stimulation - Cavalca, Alexandre Matheus Baesso [UNESP]; Brandi, Andressa [UNESP]; Fonseca-Alves, Ricardo Henrique; Laufer-Amorim, Renée [UNESP]; Fonseca-Alves, Carlos Eduardo [UNESP] (MDPI, 2022)
Canine prostate cancer (PC) is an aggressive disease, and dogs can be considered comparative models for human PC. In recent years, canine PC has been shown to resemble human castrate-resistant prostate cancer. The influx and efflux of testosterone in prostatic luminal cells are regulated by P-glycoprotein (P-gp). Therefore, human PC generally lacks P-gp expression and maintains the expression of androgen receptors (ARs). However, this co-expression has not previ-ously been investigated in dogs. Therefore, this study aimed to evaluate AR and P-gp co-expression to elucidate these protein patterns in canine prostate samples. We identified AR/P-gp double im-munofluorescence co-expression of both proteins in normal luminal cells. However, in canine PC, cells lack AR expression and exhibit increased P-gp expression. These results were confirmed by gene expression analyses. Overall, our results strongly suggest that normal canine prostate testosterone influx may be regulated by P-gp expression, and that during progression to PC, prostatic cells lack AR expression and P-gp overexpress. P-gp expression in canine PC may be related to a phenotype of multiple drug resistance.
Keywords: ABCB1; Comparative oncology; Prostatic disease; Testosterone